2022
DOI: 10.3389/fnins.2022.899887
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived From Mesenchymal Stem Cells: Novel Effects in the Treatment of Ischemic Stroke

Abstract: Ischemic stroke is defined as an infarction in the brain, caused by impaired cerebral blood supply, leading to local brain tissue ischemia, hypoxic necrosis, and corresponding neurological deficits. At present, revascularization strategies in patients with acute ischemic stroke include intravenous thrombolysis and mechanical endovascular treatment. However, due to the short treatment time window (<4.5 h) and method restrictions, clinical research is focused on new methods to treat ischemic stroke. Exoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 128 publications
(158 reference statements)
0
16
0
1
Order By: Relevance
“…Overcoming drug resistance and expanding the clinical application of conventional drugs are also crucial. [ 338 ] Despite insufficient information to translate EV therapy into clinical practice, because only one clinical trial adopting EVs to treat ischemic stroke was reported, [ 339 ] currently, there are 35 clinical trials related to EV‐associated ncRNAs with diverse states, as provided at https://www.clinicaltrials.gov/.…”
Section: Discussionmentioning
confidence: 99%
“…Overcoming drug resistance and expanding the clinical application of conventional drugs are also crucial. [ 338 ] Despite insufficient information to translate EV therapy into clinical practice, because only one clinical trial adopting EVs to treat ischemic stroke was reported, [ 339 ] currently, there are 35 clinical trials related to EV‐associated ncRNAs with diverse states, as provided at https://www.clinicaltrials.gov/.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes carry numerous molecules, such as proteins, mRNAs and other RNA species, which are thought to be of paramount importance for intercellular communication (Li et al 2021 ). For treating ischemic stroke, stem cells-secreted exosomes could be a prospective therapeutic choice due to the unique properties, including low immunogenicity and stable biological characteristic (Xiong et al 2022 ). Plenty of researches have also implied that bone marrow mesenchymal stem cell-derived exosomes (BMSC-Exos) might supply a therapeutic strategy for relieving neuroinflammation after cerebral I/R injury (Liu et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The MSC-CM contains bioactive factors including exosomes and soluble factors such as neurotrophic factors, angiogenic factors, immunosuppressive factors, and other regenerative agents [25][26][27]. Exosomes are extracellular vesicles that can be secreted by various types of mesenchymal stem cells including human umbilical cordderived mesenchymal stem cells [28]. They are one component of MSC-generated conditioned medium (CM) and contain numerous biologically active genomic and nongenomic molecules, including DNA, miRNAs, various proteins, enzymes, and lipids, which can influence the biological activity of cells via paracrine or autocrine pathways.…”
Section: Introductionmentioning
confidence: 99%
“…They are one component of MSC-generated conditioned medium (CM) and contain numerous biologically active genomic and nongenomic molecules, including DNA, miRNAs, various proteins, enzymes, and lipids, which can influence the biological activity of cells via paracrine or autocrine pathways. It has been indicated that MSC-conditioned medium or its components mediate some biological actions of MSCs [ 27 , 28 ]. Several studies found that these bioactive factors are capable of repairing tissue in a variety of tissue/organ damage conditions [ 26 , 29 ].…”
Section: Introductionmentioning
confidence: 99%